Criteria for C-Check Maintenance Service Provider Selection - Chark Tingsabhat; Wichitra Chamlongrath; Chote Limsintaropas (International Journal of Supply Chain Management, 2021)
Abstract— The objective of this paper was to determine the criteria for selection of C-Check maintenance service provider for a Thai-Singaporean low cost airline. To identify the significant criteria, the documentary studies from reviewing ten related researches in scholarly literatures were conducted and then developed the semi-structure interview guide. Based on results of the interviews of four key informants, who are the top managerial level officers of the airline company, from the competing values of roles and responsibilities, the supplier selection criteria were examined and scored by using the weighted factor rating method. The results revealed 4 significant criteria being used as a framework for the C-Check maintenance service provider selection; these are quality, cost, delivery and compatibility. However, the result confirmed that quality is a must for C-Check maintenance in compliance with the restriction of the aviation industry.Keywords— Aviation Industry, Maintenance Supplier Selection, Factor Rating Method